A ironia em foco: conhecendo as crônicas de Mário Prata - Amorim, Inessa Rosa de (2012)
The present work deals with, initially, the fictional character of the disease, its origin and related to the perception of time, constituting a form of narration that blends history and literature as a genre border, with social and political characteristics. Guided by some theoretical discourse about the irony, structural feature of the work of Mário Prata, as well as the comic element. We will also, theoretically, on the formation of national identity, the figure of the Indian and his literary representation, like the modernists, influencers Mario Prata.Since then, our work back to the analysis of some chronicles the author\'s work retained the hundred best chronicles (which are actually 129), in order to understand the texts as narratives of many meanings. We showed traces of irony in the book, exploring the search for the construction of Brazilian identity.